Morphological Characteristics of the Mediophyceae Diatom Lampriscus cf. shadboltianus var. crenulatus Collected from Gili Meno, Indonesia - Rachman, Arief; Widiarti, Riani; Sukotjo, Setiarti; Wells, Mark (UI Scholars Hub, 2026)
Diatoms are the most common and abundant microalgae group in seawater, with an estimated 200 genera and 200,000 species categorized into three distinct taxonomic classes: Mediophyceae, Bacillariophyceae, and Coscinodiscophyceae. This study describes the morphological characteristics of Lampriscus GM052022, a diatom belonging to the Mediophyceae family, which was collected from Gili Matra, Lombok, Indonesia. Analysis using light microscopy (LM) and electron microscopy (EM) showed that the morphological characteristics of the Lampriscus GM052022 specimen are similar to those of Lampriscus shadboltianus var. crenulatus due to the distinct crenulation lines on the frustule, which differentiate this variation from Lampriscus shadboltianus. However, the presence of distinct morphological features in this diatom specimen from Gili Meno suggests that it might not be L. shadboltianus var. crenulatus. The triangular spines (spinules) observed on the Lampriscus GM052022 valve surface have not been previously documented. However, whether the presence of spinules is a sign of different taxa or a result of polymorphism within the species or variation cannot be confirmed. Due to this characteristic, Lampriscus GM052022 is given the temporary name L. cf. shadboltianus var. crenulatus. The next step will be to conduct genetic analyses to confirm whether these morphological differences support the separation of this Gili Meno Lampriscus specimen into a new species (sp. nov.) or variation (var.).